“Material didáctico con recursos naturales para estimular la psicomotricidad fina en niños de 4 a 5 años” - Tiban Tisalema, Pamela Elizabeth (2024)
The present research project highlights a deficiency in fine psychomotor stimulation among 4 to 5-year-old children in four educational institutions. In response, the objective is to design didactic material using natural resources to enhance fine psychomotor skills in these children, contributing to their holistic development. The qualitative approach guided this exploratory and descriptive research, employing interview and observation techniques on 62 children and 4 preschool teachers from four educational institutions. The research results entail the design of didactic materials with natural resources to develop fine psychomotor skills in children by identifying activities closely related to the skills expected at this age. In conclusion, based on reliable theoretical and conceptual sources, the research emphasizes the importance of stimulating fine psychomotor skills using didactic materials incorporating environmental elements, providing a scientific foundation. The 2023 academic period diagnosis reveals deficiencies in children's fine psychomotor skills, leading to a proposal to improve and address these difficulties. Expert validation confirms the appropriateness of the proposed materials for children and underscores the significance of didactic material in the learning process.